Ribosomal DNA harbors an evolutionarily conserved clock of biological aging - Wang, Meng; Lemos, Bernardo (Genome Research, 2019)
The ribosomal DNA (rDNA) is the most evolutionarily conserved segment of the genome and gives origin to the nucleolus, an energy intensive nuclear organelle and major hub influencing myriad molecular processes from cellular metabolism to epigenetic states of the genome. The rDNA/nucleolus has been directly and mechanistically implicated in aging and longevity in organisms as diverse as yeasts, Drosophila, and humans. The rDNA is also a significant target of DNA methylation that silences supernumerary rDNA units and regulates nucleolar activity. Here, we introduce an age clock built exclusively with CpG methylation within the rDNA. The ribosomal clock is sufficient to accurately estimate individual age within species, is responsive to genetic and environmental interventions that modulate life-span, and operates across species as distant as humans, mice, and dogs. Further analyses revealed a significant excess of age-associated hypermethylation in the rDNA relative to other segments of the genome, and which forms the basis of the rDNA clock. Our observations identified an evolutionarily conserved marker of aging that is easily ascertained, grounded on nucleolar biology, and could serve as a universal marker to gauge individual age and response to interventions in humans as well as laboratory and wild organisms across a wide diversity of species.